Reliability of an Item Set Assessing Indoor Climate in Offices—Results From Field Studies and Laboratory Research - Schakib-Ekbatan, Karin; Lechner, Sabine; Schweiker, Marcel (Frontiers in Built Environment, 2019)
Assessing building user needs and preferences is widespread and often questionnaire surveys are applied in order to assess environmental perception and satisfaction. A central question in this context is the quality of the questionnaires used, but little is known regarding their reliability. The present study addresses interdisciplinary aspects such as engineering and psychological sciences to answer the questions: Are the same item sets applicable in various settings (e.g., seasons)? Is there any difference in the reliability of item sets assessing user satisfaction in field vs. laboratory research? In the present study, reliability analyses of an item set regarding satisfaction with indoor climate including the ASHRAE thermal sensation scale (single-item) as well as the thermal preference question were conducted with respect to season, office type, age group, and sex. Field data were gathered via post occupancy evaluation from 46 office buildings in Germany. Additionally, comparable items from laboratory research were subjected to a reliability analysis. Results revealed predominantly good to excellent Cronbach's alpha values for the field studies. The values from the laboratory study were lower, although comparable (acceptable), partly due to the differences in variation in responses in field vs. laboratory settings. Results showed that questionnaires assessing user's satisfaction need to be set in relation with the given context for reliable interpretation. Further research could validate our results with larger samples for laboratory data. Interdisciplinary research is necessary in order to further develop methodological approaches in the field of user comfort research.